Defect structure of ultrathin ceria films on Pt(111): Atomic views from scanning tunnelling microscopy - Grinter, D.C.; Ithnin, R.; Pang, C.L.; Thornton, G. (Amer Chemical Soc, 2010)
Atomically resolved scanning tunnelling microscopy (STM) images have been obtained on ultrathin films of CeO(2)(111) supported on Pt(111). The ultrathin films were grown in two ways, by reactive deposition in an oxygen atmosphere and by postoxidation of Ce/Pt surface alloys. STM results are compared with previously reported high-temperature STM and noncontact atomic force microscopy (NC-AFM) images of the native CeO(2)(111) surface. The similarity between these images is striking and allows a number or defects and adsorbates in our ultrathin film to be assigned. Moreover, the similarity in structure between the native oxide and the ceria ultrathin film indicates that is an excellent topographic mimic of the native oxide.